Vigas compostas madeira/concreto - Luciana Nunes Magalhaes (1997)
This work is concerned with the experimental study of the "T" beams made out of wooden flange and reinforced concrete web under flexibility. A bibliographic review of the national and international literature on mixed beams has been done, while developing this work and publications directly connected with the matter have been emphasized. Characterization tests of the used materials have been done - wood, concrete and connector - and, later, tests and analysis of the prototype of the composed beams have been done. Next, a comparison of the obtained results on experimental tests has been made by using the values of a numerical analysis of the beams with the finite elements method. Characteristic values of the component materials are shown in this expalnation as well as the values of the deformations, desplacements and determination of the last load of the beams that were obtained from the tests.